Juridical Overview of the Application of the Caning Law in the Province of Nanggroe Aceh Darussalam from the Human Rights Perspective: Tinjauan Yuridis Penerapan Hukum Cambuk di Provinsi Nanggroe Aceh Darussalam Dalam Perspektif HAM - Mardiana, Nana; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and explain the application of caning in Aceh in terms of human rights. Since the issuance of the legal instrument of Aceh Qanun Number 6 of 2014 there have been pros and cons in the community regarding this punishment. This research method uses normative or doctrinal, the data collection process is carried out by reviewing literature that is relevant to the problems written by the author. The result of this research is that the caning punishment in Aceh cannot be said to violate human rights. Because in its implementation it is very concerned about the safety aspect for convicts of whipping. In contrast to imprisonment, the caning sentence after the execution process of the convict can immediately return to normal activities and caning can teach the community not to commit violations.